2017
DOI: 10.1186/s12879-017-2417-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the patient and health system impacts of alternative xpert® MTB/RIF algorithms for the diagnosis of pulmonary tuberculosis in Addis Ababa, Ethiopia

Abstract: BackgroundTo reduce global tuberculosis (TB) burden, the active disease must be diagnosed quickly and accurately and patients should be treated and cured. In Ethiopia, TB diagnosis mainly relies on spot-morning-spot (SMS) sputum sample smear analysis using Ziehl-Neelsen staining techniques (ZN). Since 2014 targeted use of xpert has been implemented. New diagnostic techniques have higher sensitivity and are likely to detect more cases if routinely implemented. The objective of our study was to project the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Of the remaining 33, twenty studies were excluded due to lack of effectiveness data [ S4 Table ]. Finally this review included 13 studies from which data were extracted; four of the included studies compared LED-FM with ZN [ 13 , 25 , 26 , 27 ] and seven studies compared ZN with GeneXpert [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 33, twenty studies were excluded due to lack of effectiveness data [ S4 Table ]. Finally this review included 13 studies from which data were extracted; four of the included studies compared LED-FM with ZN [ 13 , 25 , 26 , 27 ] and seven studies compared ZN with GeneXpert [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 13 studies, seven were conducted in Africa [ 25 , 28 , 31 , 32 , 34 , 35 , 36 ] of which four were from South Africa [ 25 , 31 , 32 , 36 ], one was a multi-centric study which included Botswana, Lesotho, Namibia, South Africa and Swaziland [ 34 ], one from Zambia [ 28 ] and one from Ethiopia [ 35 ] ( Table 1 ). Four studies were conducted in Asia with one each from India, China, Hong Kong and Thailand [ 13 , 26 , 27 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…GeneXpert machines are therefore needed to improve their distribution. Tesfaye et al [17] also observed that there is shortage and poor distribution of GeneXpert machines in Sub-Saharan Africa and suggests that other cheaper alternatives are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients used to be diagnosed for TB using the spotmorning-spot smear strategy, but now they are diagnosed using the spot-spot strategy and chest radiographs [10].…”
Section: Study Settingmentioning
confidence: 99%